Produz@ideia– An approach project to develop entrepreneurship in primmary schools. - Paiva, Teresa (2014)
The greatest barriers to entrepreneurship are the fear of risk and poor entrepreneurial culture of the population. These factors are clearly identified in Portugal, in particular, due to cultural characteristics, because the fear of failure that typically an entrepreneur has to pass is a strong barrier difficult to be overcome. Also being an entrepreneur is socially very penalized, which is not the case, for example in United States culture. In spite of a poor entrepreneurial culture and subsequent difficulties in this area, the Portuguese people are extremely creative and with some guidance they reach their dreams easily. In this sense our project proposes the development of activities to be implemented very early on and empower the entrepreneurial attitude. Therefore, we consider that the elementary school has unique characteristics to the possible introduction of this project, in particular when we hook up with higher education institution connected to the professional practice teaching methodology, the HEI, namely Polytechnic Institutes. It’s our intention, consequently, to create a project that consists in stimulating children's creativity to the design of a product, service and/or machine, that children consider important that exists and where, later, teams of teachers and students of a Polytechnic HEI will build/ implement the selected ideas. We pretend to develop our project based on the notion that entrepreneurship is all about the ability of being able to have an idea or dream and put into action is a competence that relies on a problem-based learning process. This methodology, here, will begin with the young children dream explored through creativity and ends with the implementation of the solution/ idea. This empowerment of our children and young people will make them more able to risk and daring themselves to develop their ideas in the future. Thus we are contributing to a better and sustainable future of our society.